Racial Disparities between the Sex Steroid Milieu and the Metabolic Risk Profile - Arlette Perry; Xuewen Wang; Ronald Goldberg; Robert Ross; Loreto Jackson (Journal of Obesity)
Aims and Method. The present study examined the relationship between the metabolic risk profile (MRP) and total testosterone (TT) and free testosterone using the free androgen index (FAI) and sex hormone binding globulin (SHBG) in 36 Caucasian American (CA) and 30 African-American (AA) women volunteering for a weight loss study. Results. After controlling for age, significant relationships were found between TT and diastolic blood pressure (P=.004 and P=.015 in CA and AA women, resp.). Additionally, total cholesterol (P=.003), low density lipoprotein cholesterol (P=.004), apolipoprotein B (P=.006), and the total cholesterol/high density lipoprotein cholesterol (P=.027) were significantly related to TT in AA women only. In CA women, similar measures of glucose/insulin status related to FAI, were also related to SHBG. In both CA and AA women, SHBG was related to waist (P=.031 and P=.022 resp.). Conclusion. Our findings showed racial disparities in the relationship between the sex steroid milieu and the MRP in overweight/obese CA and AA women.